Solution and in silico studies on the recombinant lectin from Cicer arietinum seeds - Wakankar, Madhurima S.; Krishnasastry, Musti V.; Jaokar, Tulika M.; Patel, Krunal A.; Gaikwad, Sushama M. (International Journal of Biological Macromolecules, 2013)
The Cicer arietinum seed lectin was cloned and expressed in Escherichia coli and purified in active form. Conformational characterization of the recombinant lectin (rCAL) was performed using biophysical and bioinformatics tools. Thermal denaturation of rCAL caused rapid secondary structural rearrangements above 50 degrees C and transient exposure of hydrophobic residues at 55 degrees C, leading to aggregation. Treatment of rCAL with GdnHCl resulted in unfolding followed by dissociation of the dimer. The single tryptophan in rCAL present on the surface of the protein is surrounded by hydrophobic and acidic amino acids and exists as different conformers. The experimental observations correlated well with the structural information revealed from the homology model of rCAL. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aggregation; BL21-CodonPlus (DE3)-RIL cells; Cicer lectin; Homology model; Steady-state and time resolved fluorescence; Unfolding